Armutsbekämpfung durch Reduktion von Korruption: eine Rolle für Unternehmen? - Klaus Beckmann; Carsten Gerrits (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2008)
We consider an argument that it might be helpful to combat poverty in developing countries indirectly by enlisting firms' help (as corporate citizens) in reducing corruption. It turns out that this argument crucially depends on a fair number of presmises, including (a) a common interest of firms in reducing bribes, (b) the absence of positive effects of corruption on society at large and (c) the cost-effectiveness of formal institutions designed to combat corruption. In all three regards, we explain a number of reservations, both theoretical and empirical. Some tentative institutional policy recommendations ensue.
urn:nbn:de:gbv:705-opus-17196
Keywords: D730; 330; Armutspolitik; Korruption; Kriminalpolitik; Multinationales Unternehmen; Corporate social responsibility; Entwicklungsländer